Culture, society and politics in central Asia and India - Singh, Karan; Vohra, N. N. (ed.) (Delhi Shipra Publications, 2019)
Preface. Introduction. An Overview. Tradition and History: Philosophy, Relogion and Literature. Archaeological and Historical Findings and Perspectives.Cultural and Economic Exchanges: Arts and Crafts, Artisans and Merchants. The Nineteenth and Twentieth Centuries: Culture and Religion; Political and economic Contacts. The Post War Era: Impact of Globalisation. National Identity and the Revival of Traditional and Popular Culture. The Challenges and Prospects of Cooperation. Facing a New Millennium.
Keywords: IAS as an editor; 1959 batch; Culture and society; Central Asia and India